Marketing Strategy of Sharia Banking Products to Attract Public Interest in Transactions: Case Study at Jambi Regional Development Bank (BPD) Sungai Sungai Branch Office - Mega Ilhamiwati; Yosi Maytesa (AL-FALAH : Journal of Islamic Economics, 2020)
Purpose:. Marketing is not difficult nor complicated. But, when it is not paid attention, it may impede the growth of the sharia (syariah) bank. Let alone with the dominant muslim population, the region development bank (BPD) will need to implement marketing strategies that will attract people to use syariah service.Design/Method/Approach : This field research uses a qualitative research approach because it leads to holistic circumstances and individuals.Findings:  According to the results of the study, the marketing plan for syariah products in the syariah services of the Jambi Regional Development Bank (BPD) branch office Sungai Penuh offered to the customers is based on the needs of each product, in PLC (Product life cycle) it means the offers depend on what product is at the time. The strategies implemented in the Jambi Regional Development Bank (BPD) syariah services in Sungai Penuh branch office is to priotitize customers with low-cost fund rather than the deposits with high-cost fund. Of course,the implementation of those strategies will meet various obstacles in the development of the upcoming products. However, BPD also has contributing factors in selling its syariah products.Originality/Values: Case study—BPD Jambi is differenciation study when compare to others.